Epidemiological Trends in Asthma - Malcolm R Sears (Canadian Respiratory Journal)
Many markers of asthma morbidity have shown substantial increases over the past two decades, including family physician visits, use of anti-asthma medications, emergency room visits and hospital admissions. The reported prevalence of diagnosed asthma and of wheezing has increased, especially in children, with accompanying evidence of increased atopy and increased airway responsiveness. Allergen exposure and parental smoking are significant risk factors for childhood wheezing, whereas the influence of outdoor air pollution is uncertain. Increasing use of beta-agonist treatment, which appears to increase the severity of asthma by increasing early and late responses to allergen, may contribute to increased morbidity and mortality, especially if potent beta-agonists are used. Risk factors for asthma mortality include age, smoking, allergy and airway lability, as well as over-reliance on beta-agonists and poor compliance with other aspects of treatment. Following withdrawal of the potent beta-agonist fenoterol in New Zealand, both hospital admissions and mortality from asthma fell abruptly. Continued patient and physician education, with emphasis on avoidance of risk factors and use of appropriate treatment, should reduce morbidity and mortality from asthma in Canada.